Mechanics and manufacturers in the early industrial revolution : Lynn, Massachusetts, 1780-1860 - Faler, Paul G. (Paul Gustaf), 1940- (SUNY series in American social history., 1981)
Lynn, Massachusetts, once the leading shoe manufacturing city of the United States, was in many ways a model of the industrial city that much of America was to become. This study of the early industrial revolution in Lynn focuses on the journeymen shoemakers, leading participants in the making of the institutions, ideas, and events that form central themes in the history of working people in America. Spanning the time period from just after the American Revolution to the Civil War, it places special emphasis on the social changes that accompany industrialization, and the impact of those changes on workers. It examines the shoe industry and shoemaking in detail: wages and conditions of work, social clubs and political parties, strikes as well as schools, and trade unions as well as temperance societies. It also explores property ownership and social mobility, the origins and nature of class consciousness and class ideology, and the relations between workers and manufacturers across the spectrum of social institutions. This study of the industrial revolution in a single community combines labor history and social history, revealing the fullness and breadth in the experience of the working people.